Impact of Globalization On Education and Gender in The Democratic Republic of Congo - Sifa Bura Huguette (Universitas Lampung, 2021)
Seen as a bittersweet gift to the world today, especially in developing countries, globalization has had both positive and negative impacts on Africans, and especially on the people of the Democratic Republic of Congo. Social, political and economic development are the first sectors of the country’ structural changes most affected by the latter in several aspects. Despite the resources of Congo have played an important role in globalization around the world; more so in the world outside Congo. Through the death of millions of people, socioeconomic and psychological challenges, the Congolese people have had to pay a very high price simply to sustain globalization. While expected to help address these challenges, education and gender in the Congo have struggled to face the repeated challenges of globalization effects. This study aims to explore how globalization affects the quality of education and gender when a country is constantly under the challenges of war, political and economic crises, and what is being done about it. Qualitative analysis and documentary research method have been used for data collection and desk review. Adjustment programs suggested by external have showed that the globalization has affected women and men development differentially, with a larger costs assumed by women. Yet girls still suffer signiﬁcant deprivations and inequalities, many of which result from the persistent gender discrimination faced by girls and women everywhere. To cope with this, reform measures continue to be adopted with a view to economic recovery, with special focus on open education for all by improving access, equality and equity, job creation and reducing poverty in order to improve the living conditions of each.Keywords: Globalization, Education, Gender.DOI: http://dx.doi.org/10.23960/jiip.v3i1.23268